Analisis Berbagai Faktor yang Berpengaruh terhadap Kinerja Pegawai Dinas Perindustrian dan Perdagangan Provinsi Papua Barat - Fari Yanti Ratang; Balthazar Kambuaya; Halomoan Hutajulu (Universitas Cenderawasih, 2023)
Research on influence The purpose of this study was to analyze the influence of budgetary participation variables, quality of human resources, internal control systems, and utilization of information technology, on the performance of employees of the Office of Industry and Trade of West Papua Province, which has been carried out. The purpose of this study was to analyze the influence of these four variables on the Performance of the Office of Industry and Trade of West Papua Province. This research was conducted at the Office of Industry and Trade of West Papua Province. The population of this study were 67 civil servant respondents. The sample selection method used was purposive sampling. The analytical method used is hypothesis testing.Â The results showed that the four variables: the influence of the variable participation in budget preparation, the quality of human resources, the internal control system, and the use of information technology, were positively correlated with the performance of employees at the West Papua Province Industry and Trade Office. Increasing these four variables can encourage increased employee performance.